The dynamics of systematic structure of Park Trostjanets dendroflora - O.O. Iljenko; V.A. Medvedev; M.A. Rahіnskaja (Інтродукція Рослин, 2011)
It is investigated the dynamics of floristic composition, systematic structure and a variety of the alien and local species of woody plants of Dendropark Trostjanets in 1965–2008.